Demonstration of synergistic catalysis in Au@Ni bimetallic core-shell nanostructures - Vysakh, A. B.; Babu, Chinchu Lizen; Vinod, C. P. (Journal of Physical Chemistry C, 2015)
Coreshell bimetallic nanoparticles comprised of gold core and varying nickel shell have been synthesized, and their synergistic effect in catalysis is explored through catalytic hydrogenation of p-nitrophenol and p-nitrothiophenol. A clear evidence for synergism in Au@Ni core-shell nanoparticles having an ultrathin Ni shell (1-2 nm) around a Au core (6-10 nm) resulting in enhanced catalytic activity is observed. The rates observed from a thin nickel shell are higher than monometallic Au or Ni nanoparticles of similar size or with a thicker Ni shell of 6-8 nm.